Biotransformasi Limbah Ikan Menjadi Bahan Pakan untuk Ruminansia - Efka Aris Rimbawanto; S.N.O. Suwandyastuti; Sri Rahayu (Agricultural Faculty, 2012)
Biotransformation of fish waste as feed matter for ruminantABSTRACT. Fish waste (head, viscera and tails) which ensilage with saccharomyces sp and lactobacillus sp, had a high quality and protein content of about 53,18 0,83% and a good aroma. An experiment have been conducted by experimental method with in sacco trial and in vivo trial. The treatment tested were 4 kind of protein source : (1) fish waste silages mixed with tapioca ; (2) fish waste silages mixed with rice bran ; (3) soy bean kernels and (4) fish meal. The in sacco trial was carried out on 3 fistulated cows, to study the rate of protein degradability in the rumen. The in vivo trial was carried out by Completely Randomized Design on 16 heads of fat tail rams. The variable measured were: rumen fermentation product (VFA and N-NH3); energy and protein digestibility; daily body weight gain of the rams. The experiment showed, that the source of protein use have no significantly effect upon VFA both on the VFA total and individual VFA (acetate, propionate and butyrate). The highest propionate reach by soya bean kernels (P 0.01). Based on the all variables measured, it was indicated the silage of fish waste can be used to substituted of soya bean kernels or fish meal in the ration of sheep.